The Capacitated Vehicle Routing Problem: Stronger bounds in pseudo-polynomial time - Letchford, Adam N.; Salazar-González, Juan-José (European journal of operational research, 2019)
•New mathematical models for the Capacitated Vehicle Routing Problem.•Lower bounds computable in pseudo-polynomial time.•Column-generation technique to solve vehicle routing problems with capacity constraints. The Capacitated Vehicle Routing Problem (CVRP) is a classic combinatorial optimization problem for which many heuristics, relaxations and exact algorithms have been proposed. Since the CVRP is NP-hard in the strong sense, a natural research topic is relaxations that can be solved in pseudo-polynomial time. We consider several old and new relaxations of this kind, all of which are based on column generation. We also analyze the effect of adding some known inequalities. Computational experiments demonstrate that the best of our new relaxations yields extremely tight lower bounds.